2017
DOI: 10.1002/ldr.2726
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture Had a Poor Impact on the Soil Porosity of Veneto Low‐lying Plain Silty Soils after a 5‐year Transition Period

Abstract: Conservation agriculture practices have been proposed as a set of techniques for improving soil structure properties and related ecosystem services. This study compared conservation agriculture (CA) practices (no‐tillage, cover crop and residue retention) and conventional intensive tillage system in order to evaluate their effects on total porosity, pore size distribution, pore architecture and morphology. The experiment was set up in 2010 on four farms of the low‐lying Veneto Region plain characterized by sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…We argue that the decrease of bulk density (Table 4), which could be a signal of enhanced porosity, was the consequence of conventional and light ploughing that broke down the superficial layer after the no cultivation period. A slow reaction to improve soil structure properties in similar silty soils with low organic carbon content was also observed in previous studies, [53], suggesting that long-term strategies to increase the chemical and physical soil fertility are required.…”
Section: Soil Organic Matter and Stability Indexessupporting
confidence: 75%
“…We argue that the decrease of bulk density (Table 4), which could be a signal of enhanced porosity, was the consequence of conventional and light ploughing that broke down the superficial layer after the no cultivation period. A slow reaction to improve soil structure properties in similar silty soils with low organic carbon content was also observed in previous studies, [53], suggesting that long-term strategies to increase the chemical and physical soil fertility are required.…”
Section: Soil Organic Matter and Stability Indexessupporting
confidence: 75%
“…The opposite was observed by Pires et al (2017) for a Brazilian Rhodic Ferralsol of clay texture under long term ZT, using X-ray CT with an image acquisition resolution of 20 μm. Using a combination of mercury intrusion porosimetry and X-ray CT, Piccoli et al (2017) concluded that a conservation agricultural system comprised of no-tillage, cover crops and residue retention in silty soils in the Veneto Region in Italy did not significantly change macroporosity (>26 μm), but increased ultramicroporosity (0.1–5 μm), compared to conventional intensive tillage after five years of implementation. The authors attributed the slow reaction to conservation agriculture in macroporosity to poor aggregate stability and low soil organic carbon content in the studied soils.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously postulated that the limited amount of non‐complexed OC available for interaction with clay minerals and the low ratio between clay and silt particles could prevent the formation of a resilient structure in silty soil in the Veneto region (Piccoli, Schjønning, et al, 2017). On the other hand, after 3 to 5 years of CA, an enhanced humification process produced more polycondensed humic substances (Piccoli et al, 2016) and was concurrently associated with an increase in ultramicroporosity, for instance, 0.1–5.0 μm (Piccoli, Camarotto, Lazzaro, Furlan, & Morari, 2017), which is strictly linked to SOC physical protection (Lugato, Morari, Nardi, Berti, & Giardini, 2009; Simonetti et al, 2017). These results suggested that a virtuous cycle between SOC and soil structure was initiated in the CA system, leading to soil C pool stabilization, well‐developed macropore systems and, in turn, enhanced soil functions and related ecosystem services in the longer term.…”
Section: Discussionmentioning
confidence: 99%